EMPIRICAL RESEARCH OF COLLOCATIONS IN FOREIGN LANGUAGE LEARNING - Adamcova, Silvia (Advanced Education, 2020)
This scientific paper presents a corpus-based investigative research of German collocations; in text comprehension, a new method for identification of collocations is presented, as well as a scientific discussion of the types of collocations for which this new analysis method is suitable. The article further explores the consequences of using collocations and their translation into other languages on communication in foreign language teaching. It was examined how the students of foreign languages in Slovak universities (non-philological courses of studies) can deal with the collocations in their future profession (as translators or experts in a professional language) after their linguistic studies and whether they are able to actually implement this foreign language competence in the future. Although vocabulary work is developed as a primary competence among foreign language learners, some areas of studies lack current, creative and innovative teaching materials, especially in the didactic field of comparative collocation research. The results of our research projects promote the acquisition of foreign language skills and help teachers develop and use new methods in their work.